Effectiveness of Green Roofs and Green Walls on Energy Consumption and Indoor Comfort in Arid Climates - Sherine M. Wahba; Basil A. Kamel; Khaled M. Nassar; Ahmed S. Abdelsalam (Salehan Institute of Higher Education, 2018)
Increased urbanization have many negative effects on human well-being, city infrastructure, electricity usage and the increase of indoor temperatures. A solution may be to retrofit existing buildings, with implementing a vegetated layer to roofs and walls, this may enhance building performance, reduce consumption and improve indoor comfort. Cities with tall buildings may be more adequate to implement a green-wall as it have more area to make impact. This paper examines the energy reduction advantages of adding greenery on buildings in the hot arid climate of Egypt by considering three typical types of residential buildings in the city of Cairo as a case study. Designbuilder software was selected to stimulate the buildings chosen in this research. The results shows that an extensive soil thickness of 15cm performs better in the arid climates. electricity consumption for the base case is 52 kWh/m2 annually when used a traditional external envelop and dropped to 43 kWh/m2 when a vegetated layer added to the whole building (roof & wall), annual electricity consumption reduced by 17% to 25% per annum when added a vegetated layer. In addition to enhancing the indoor thermal comfort by 3 PMV values and indoor air temperature by 5°C.